You are on page 1of 16

Differentiation C3

Specifications.

Find the derivatives of trigonometric, logarithmic and exponential functions.

Work will also include turning points and the equations of tangents and

normals.

The following differentials must be learnt.

Function Differential
lnx 1
x
emx memx
Sin t Cos t
Cos t -Sin t
Tan t Sec2 t
Sec t Sec t Tan t
Cot t -Cosec2 t
Cosec t -Cosec t cot t
Sinn t nSinn-1 t Cos t
Cosn t -nCosn-1 t Sin t
Sin (g(t)) g’(t)Cos (g(t))
Cos (g(t)) -g’(t)Sin (g(t))
Tan (g(t)) g’(t)Sec2 (g(t))

Chain Rule

If y is a function of v and v, in turn, is a function of x, then:

C3 1
dy dy dv
= ×
dx dv dx

Product Rule
d dv du
( uv) = u + v
dx dx dx

Quotient Rule
du dv
v −u
d  u dx dx
  =
dx  v  v 2

Composite Functions

y = (mx + c)n

dy
= nm ( mx + c ) n −1
dx

y = (f(x))n

dy
= nf' ( x ) × ( f( x )) n −1
dx

The following example covers most of the ideas introduced above.

Example 1

C3 2
Differentiate the following with respect to x simplify your answer as far as

possible.

a) (x + ln 4x)7

b) 6 sin2x + sec 2 x

d) x5 e5x + 5

cos5x5
e)
3x

d
a) (x + ln 4x)7
dx

By chain rule

If y = (x + ln 4x)7 let u = (x + ln 4x)

du 1 1
So y = u7 =1+ not
dx x 4x

dy
= 7u6
du

C3 3
So

d  1
(x + ln 4x)7 = 7u6 ×  1 + 
dx  x

 1
= 7(x + ln 4x)6  1 + 
 x

If y = 6sin2x let u = sinx

du
then y = 6u2 = cos x
dx

dy
= 12u
du

By chain rule

dy dy du
= ×
dx du dx

= cos x × 12u

= 12cos x sin x = 6 sin 2x

So finally:

C3 4
d
(6sin2 x + sec2x) = 6 sin 2x + 2 sec 2x tan 2x
dx

c)

The rule for differentiating products is to differentiate the first and

times it by the second and then add the differential of the second times

by the first. Or in symbols:

d(uv) du dv
=v +u
dx dx dx

d 11
(x tan13x) = 11x10 tan13x + 13x11 sec2 13x
dx

d 5 5x + 5
d) (x e )
dx

power on the e and bring it to the front.

d 5 5x + 5
(x e ) = 5x4 e5x + 5 + 5x5 e5x + 5
dx

= 5x 4 e5x + 5 (1 + x)

C3 5
d  cos5x5 
e)  
dx  3x 

question says specifically to use the quotient rule.

d  cos5x5  d  x −1 cos5x5 
 =  
dx  3x  dx  3 

x −1
Let u = v = cos5x5
3

du −x −2 dv
= = −25 x 4 sin 5x 5
dx 3 dx

Therefore:

 cos 5x 5 
d 
 3x  = − x cos 5x 5 − x × −25x 4 sin 5x 5
−2 −1

dx 3 3

cos 5x 5 25x3 sin 5x 5

=− +
3x2 3

Example 2
dy
Given that x = 8sin(7y + 3), find .
dx

C3 6
dy 1
=
The only thing that is new here is that dx dx
dy

x = 8sin(7y + 3)

Don’t forget to write the (7y + 3) in

dx
= 56cos(7y + 3)
dy

dy 1 sec(7y + 3)
= =
dx 56cos(7y + 3) 56

Equations of tangents and Normals

Example 3
1 x
The curve with equation y = e meets the y axis at the point A.
6

the point C. Prove that the x coordinate of C is ln 6 + 17.5 and find

the y coordinate of C.

especially in this case where there are quite a few lines.

C3 7
8

6 Normal
B

4 C
y=1/6ex

Tangent
A
0
-5 0 5 10 15 20 25 30 35

1
y=-26 ex
Normal
a) First find at x = ln36
Tangent at x = 0
dy 1 x
= e
dx 6

1
At A, x = 0 therefore the gradient is as is the y coordinate.
6

y = mx + c

1 1
= ×0+c
6 6

Therefore

1 1
y= x+
6 6

and hence 6y = x + 1

b) Find the equation of the normal at the point B with x coord of ln 36.

1 x
From part (a) the gradient function is e hence the gradient at B is 6 and
6

C3 8
−1
so the normal gradient is . (y coord also 6)
6

y = mx + c

− ln36
6= +c
6

−x ln36
y= +6+
6 6

The normal then meets the tangent from part (a) at the point C.

1 1 −x ln36
x+ = +6+
6 6 6 6

2x = 35 + ln36

1
x = 17.5 + ln36 = 17.5 + ln 6
2

Therefore the y coordinate can be found by substituting x = ln 6 + 17.5 into

6y = x + 1.

6y = ln 6 + 17.5 +1

1 37 
y= ln 6 + 
6 2 

C3 9
Example 4
7
The curve c has equation y = 4x 2 − ln 4x , where x > 0. The tangent at the

point C where x = 1 meets the x axis at the point A.

9 + ln 4
Prove that the x coordinate of A is .
13

7
y = 4x 2 − ln 4x

dy 5
1
= 14x −
2
dx x

y = mx + c

4 – ln4 = 13 + c

The line meets the x-axis at the point where y = 0. Therefore:

13x – 9 – ln4 = 0

9 + ln 4
x=
13

C3 10
Differentiating Quotients

Example 5

4x2 − 16x + 7
Given that y = , x ≠ 2,
(x − 2)2

dy 18
Show that =
dx (x − 2)3

It is obvious from the question that by using the quotient rule it will be

easier to get the desired answer.

u
d   v du − u dv
 v  = dx dx
dx v 2

u = 4x2 − 16x + 7 v = (x – 2)2

du dv
= 8x − 16 = 2(x − 2)
dx dx

Therefore:

C3 11
dy (x − 2)2 (8x − 16) − (4x2 − 16x + 7) × 2(x − 2)
=
dx (x − 2) 4

=
(x − 2)3

=
(x − 2)3

18
=
(x − 2)3

Example 6

The diagram shows part of the curve with equation,

C3 12
π
y = (10x – 3) tan 3x, 0≤x<
4

that K satisfies the equation 30K – 9 + 5 sin 6K = 0

As soon as you see the word minimum your first thought should be to

differentiate and set it equal to zero.

Differentiating a product:

y = (10x - 3) tan 3x

dy
= 10 tan3x + 3(10x - 3)sec2 3x
dx

0 = 10 tan3x + 3(10x - 3)sec2 3x

sin3x 3(10x − 3)
0 = 10 +
cos3x cos2 3x

Multiply by cos2 3x

0 = 10sin3xcos3x + 3(10x − 3)

0 = 5 sin 6x + 3(10x − 3)

If x = K

30K – 9 + 5 sin 6K = 0

C3 13
A lot of the ideas outlined above are not complicated and the final example

below deals with turning points and the differential of exponential functions.

Example 7

x
y=
9 + x2

Use calculus to find the coordinates of the tuning points of C.

b) Given that
5
(
y = 1+e 4x 4
)
dy 1
find the value of at the point x = ln 3 .
dx 4

a) The curve C is to be differentiated as a quotient

u
d   v du − u dv
 v  = dx dx
dx v 2

u=x v = 9 + x2

du dv
=1 = 2x
dx dx

C3 14
dy 9 + x2 − 2x2
=
dx (9 + x2 )

dy 9 − x2
=
dx (9 + x2 )

dy
Turning points exist where = 0 therefore the numerator must equal zero
dx

By substituting these values into y we get:

x  1  −1
y=  3,  and 3, 
9 + x2  6  6 

b) Given that
5
(
y = 1+e 4x 4
)
dy 1
find the value of at the point x = ln 3 .
dx 4

This is a composite function. To differentiate it simply multiply by the

power, multiply by the differential of the bracket and then multiply by the

differential of the bracket.

C3 15
5
y = (1 + e 4 x ) 4

dy 5 1
= × 4e 4 x × (1 + e 4 x ) 4
dx 4

dy 1
= 5e 4 x (1 + e 4 x ) 4
dx

1
Let x = ln 3
4

dy 1

dx
(
= 5eln 3 1 + eln 3 ) 4

dy  1
= 15 4 4 
dx  

C3 16